Not-high before-treatment platelet reactivity in patients with STEMI:prevalence, clinical characteristics, response to therapy and outcomes. (14th October 2021) - Canonico, M E; Sanna, G D; Siciliano, R; Guarino, S; Bellandi, B; Scudiero, F; Saba, P S; Esposito, G; Alexopoulos, D; Parodi, G
Abstract: Background: Platelet reactivity (PR) has been indicated as a pathophysiological key element for ST-Elevation Myocardial Infarction (STEMI) development. In STEMI patients, PR following pharmacological treatment has been extensively studied with focus on patients with on-treatment high platelet reactivity (HPR). Patients with before-treatment not-high platelet reactivity (NHPR) have been poorly studied so far. Purpose: Aim of the study is to investigate the prevalence, clinical characteristics, response to therapy and outcomes of baseline prior to treatment NHPR among patients with STEMI undergoing primary PCI. Methods: We analysed the data from 358 STEMI patients with assessment of PR by VerifyNowbefore P2Y12 inhibitor loading dose (LD). All patients received a P2Y12 inhibitor (ticagrelor or prasugrel) LDafter baseline PR assessment. Blood samples were obtained at baseline (T0), and after 1 hour (T1), 2 hours (T2), 4–6 hours (T3) and 8–12 hours (T4) after LD. HPR was defined as Platelet Reactivity Unit values ≥208, while patients with values <208 at baseline were defined as having NHPR. Results: Overall, 20% patients had NHPR. Patients with before-treatment NHPR values were more frequently young, of male gender and more frequently smokers (p=0.005), overweight or obese (p=0.009), affected by dyslipidemia (p=0.03) and with a family history of coronary artery disease (p=0.04). Age and male gender resulted both independent predictors of NHPR, even after propensity score adjustment. The percentage of inhibition of PR after ticagrelor or prasugrel LD was similar between HPR and NHPR patients at each time point (figure 1) and residual PR was constantly lower in patients with before-treatment PRU <208 from baseline to 8–12 hours from LD (figure 2). However, patients with HPR showed worse in-hospital clinical outcomes, and the composite adverse outcome endpoint of death, reinfarction, stroke, acute kidney injury or heart failure was significantly higher (10.0% vs 1.4%; p=0.017) as compared with the NHPR group. Conclusions: A significant proportion of patients presenting with STEMI has a baseline NHPR; they are predominantly young males with a high-risk cardiovascular profile. NHPR is associated with better in-hospital outcomes as compare with patients with HPR. Further studies are needed to better understand the underlying pathophysiology in order to find out potential personalized treatments in this setting. Funding Acknowledgement: Type of funding sources: None.